A literature comparison of the life cycle assessments of wood and recycled plastic pallets: Recycled plastic pallet using a proprietary recycling process technology compared to conventional wooden pallet - Halleröd, Philip; Turefeldt, Mael (My University, 2024)
Plastic waste management is a critical issue, with lots of plastics being incinerated, a specific company offer a solution by converting plastic waste that would otherwise be incinerated into products. a proprietary recycling process technology (RPT) use this waste plastic in a proprietary process to form into new pallets. This study looks at the entire life cycles emissions for their recycled plastic pallet compared to traditional wooden pallets. Focus lies only on emissions from the two pallets that are studied, not the impact of said emissions. The proprietary technology is exclusive to the Nordic market; thus, the study look at that geographical area for both pallets. The findings are primarily based on the comparison between two life cycle assessments (LCA), one for wood pallets and one for recycled plastics, evaluating CO2-equivalent emissions across different life cycle phases. The study also considers carbon sequestration in combination with energy recovery at incineration phase for wooden pallets. It shows that wooden pallets can become net neutral, or even net negative when accounting for energy recovery with carbon sequestration. In a similar way that the RPT prevents the release of emissions through continuous recycling of plastic waste and thus also having a net-negative emission result. The result underscores the benefits of using the RPT instead of incineration, with or without energy recovery. There are however several qualifications to arrive at this result. These benefits are contingent on the implementation of a circular system to ensure the repeated recycling of recycled plastic pallets. Because of the difficulty of estimating long-term consequences, reuse of all plastic pallets is assumed for ease of comparison. Wooden pallets are more versatile, as relevant infrastructure exist everywhere, and expertise is well established
Keywords: plastic waste management; recycling; incineration; energy recovery; life cycle assessment; carbon sequestration; Recycling Process Technology; Nordic market; pallets; plastavfallshantering; återvinning; förbränning; energiåtervinning; livscykelanalys; koldioxidlagring; återvinningsprocess; pallar